Short Report of Longitudinal CGRP-Measurements in Migraineurs During a Hypoxic Challenge - Frank, Florian; Kaltseis, Katharina; Messlinger, Karl; Broessner, Gregor (Frontiers in Neurology, 2022)
Background Calcitonin gene related peptide (CGRP) plays a key role in the pathophysiology of migraine and is therefore considered a potential biomarker for primary headache disorders. The challenge remaining is establishing standardized protocols for its assessment in various extracellular compartments and identifying pathological situations associated with an increase in CGRP. Methods We performed longitudinal measurements of CGRP plasma levels in 30 volunteers with the diagnosis of episodic migraine with and without aura under controlled circumstances during an induced migraine attack under a hypoxic challenge. Blood samples were collected from a cubital vein and CGRP plasma levels measured using ELISA. Results CGRP levels varied significantly between the subjects at baseline (15.48–1,889.31 pg/ml) but were neither associated with socio-demographic data nor with headache/migraine frequency or intensity collected before hypoxic exposure. CGRP levels during hypoxia fluctuated around baseline and increased with prolonged hypoxia but did not differ significantly in subjects with migraine or headache compared to those without. However, subjects experiencing migraine without aura showed significantly higher levels than those with aura. Ictal CGRP levels were increased in females, in subjects with a negative family history regarding headaches, in those older than 30 years of age or with a recent headache attack before the experiment (p < 0.05). Conclusion CGRP plasma levels seem to be highly variable even at baseline in migraine patients and increased during hypoxic challenge and migraine attacks. This is the first in human longitudinal measurement of peripheral CGRP levels during induced migraine attacks using a highly standardized protocol.